Colonization of Supplemented Bifidobacterium breve M-16V in Low Birth Weight Infants and Its Effects on Their Gut Microbiota Weeks Post-administration - Horigome, Ayako; Hisata, Ken; Odamaki, Toshitaka; Iwabuchi, Noriyuki; Xiao, Jin-zhong; Shimizu, Toshiaki (Frontiers in Microbiology, 2021)
The colonization and persistence of probiotics introduced into the adult human gut appears to be limited. It is uncertain, however, whether probiotics can successfully colonize the intestinal tracts of full-term and premature infants. In this study, we investigated the colonization and the effect of oral supplementation with Bifidobacterium breve M-16V on the gut microbiota of low birth weight (LBW) infants. A total of 22 LBW infants (12 infants in the M-16V group and 10 infants in the control group) were enrolled. B. breve M-16V was administrated to LBW infants in the M-16V group from birth until hospital discharge. Fecal samples were collected from each subject at weeks (3.7-9.3 weeks in the M-16V group and 2.1-6.1 weeks in the control group) after discharge. qPCR analysis showed that the administrated strain was detected in 83.3% of fecal samples in the M-16V group (at log10 8.33 ± 0.99 cell numbers per gram of wet feces), suggesting that this strain colonized most of the infants beyond several weeks post-administration. Fecal microbiota analysis by 16S rRNA gene sequencing showed that the abundance of Actinobacteria was significantly higher (P < 0.01), whereas that of Proteobacteria was significantly lower (P < 0.001) in the M-16V group as compared with the control group. Notably, the levels of the administrated strain and indigenous Bifidobacterium bacteria were both significantly higher in the M-16V group than in the control group. Our findings suggest that oral administration of B. breve M-16V led to engraftment for at least several weeks post-administration and we observed a potential overall improvement in microbiota formation in the LBW infants’ guts.